Stick to Convention or Bring Forth the New? Research on the Relationship Between Employee Conscientiousness and Job Crafting - Liu, Xiayi; Yu, Ting; Wan, Wenhai (Frontiers in Psychology, 2020)
Integrating regulatory focus theory and personality literature, we develop and test a moderated mediation model to specify the underlying mechanisms and boundary conditions of the linkage between employee conscientiousness and job crafting. Two-wave data collected from 389 employees and 95 supervisors showed that: Employee conscientiousness had a positive effect on work promotion focus and work prevention focus. Employee conscientiousness was positively related to job crafting via work promotion focus, negatively related to job crafting via work prevention focus. Error management climate positively moderated the relationship between employee conscientiousness and work promotion focus, negatively moderated the relationship between employee conscientiousness and work prevention focus. The indirect relationship between employee conscientiousness and job crafting through work promotion focus and work prevention focus were more pronounced respectively when the error management climate is higher rather than lower.